Anti-oxidant Activities of a Thai Remedy in Worayokasan Scripture - Boonyuenyong, Kunsurapa; Houngiam, Katanchalee; Chaiyawatthanananthn, Pannawat (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Plant antioxidants have an important role in the prevention of many age-related diseases. A Thai medical remedy consists of 3 herbs: Terminalia chebula fruits(TC), Cyperus rotundus rhizomes (CR) and Tinospora crispa vines (TIC), following Worayokasan scripture. In the previous studies, polyphenolic TC, methanol CR and ethanolic TIC extracts had free radical scavenging activity. These results support the use of the remedy and the herbal compounds for reducing free radicals. Objectives: To investigate ethanolic and water extracts of the remedy and its plant ingredients on anti-oxidant activities and capacities. Methods: The remedy (RM) was macerated with 95% ethanol (RME) or water decoction (RMW). Dry TC, CR and TIC plants were extracted with the ethanol maceration (TCE, CRE, and TICE, respectively) or water decoction (TCW, CRW and TICW, respectively). All extracts were measured anti-oxidant activities by DPPH, FRAP and ABTS+ radical assays, and anti-oxidant capacities by total phenolic (TPC) and total flavonoid (TFC) contents. Results: RME and RMW had the anti-oxidant activities by DPPH method (EC50 = 11.00 and 53.49 µg/mL, respectively), ABTS assay (EC50 = 41.66 and 34.06 µg/mL, respectively) and FRAP values (220.78 and 228.84 mg Fe2+/g of extract, respectively), and had anti-oxidant capacities by TPC (48.16 and 64.95 mg GAE/g of extract, respectively) and TFC (116.56 and 134.06 mg QE/g of extract, respectively). Moreover, TCW showed very strong DPPH (9.43 µg/mL) and ABTS (11.40 µg/mL) activities and the highest TPC (142.15 mg GAE/g of extract). TCE and CRE had the highest FRAP value (467.14 mg Fe2+/g of extract) and TFC (182.30 mg QE/g of extract), respectively. Conclusions: The remedy and the three herbal extracts had antioxidant activities and capacities. Thus, they could be used for reducing and preventing oxidation.